The Effectiveness of Learning Media "English Club Project” for Teaching Grammar In Limited Face High School - Prabawa, Arya Tata (ETERNAL (English, Teaching, Learning and Research Journal), 2025)
The purpose of this research is to know the effectiveness of learning media “English Club Project” in teaching grammar for Senior High School students in a limited face-to-face learning policy. This research was conducted in X Science 2 class of SMAN 1 Polokarto in the academic year 2021/2022. The researcher used quantitative pre-experimental research using intact group comparison. The samples divided into 2 groups, experiment and control classes. The results showed that the usage of learning media “English Club Project” effective in teaching grammar. The use of learning media “English Club Project” helps to improve the grammar mastery of the senior high school students in the English language. This research also makes teachers have better option in order to teach in a limited face-to-face learning policy.